Pleistocene of the western part of the Kleszczów Graben based on research in the Szczerców field, Central Poland - Wachecka-Kotkowska, Lucyna; Krzyszkowski, Dariusz Krzyszkowski; Wieczorek, Dariusz (Acta Geographica Lodziensia, 2024)
This article presents an overview of the results of studies of Pleistocene deposits carried out from 2010 to 2023 in the Bełchatów Open-cast Lignite Mine, Szczerców field. Initially, studies of glacial till were conducted, but later the focus was on alluvia and lacustrine sediments. The reconstructions made use of lithopetrographic studies for the glacial tills, and for the fluvial and lacustrine sediments made use of wide-ranging palaeoecological studies (analyses of Diatoms, pollen, plant and seed macro-remnants and Cladoceran, freshwater fauna, Chironomidae communities, and studies of mineral composition, nitrogen and oxygen isotopes, anisotropy of magnetic susceptibility of the sediment). Some of the younger sediments were also disbursed using the radiocarbon method. The exposed Pleistocene profile has not been fully studied. About 400 samples from 2014 and 2017–23 are awaiting analysis, and the lower tills are being studied to determine their age, sampled in 2022.